An analysis of extreme temperature events in South Africa: 1960-2015 - Van der Walt, Adriaan Johannes (My University, 2024)
Extreme Temperature Events (ETEs), which include heatwaves, warm spells, cold waves and cold spells, have disastrous impacts on human health and ecosystems. The frequency, intensity, and duration of ETEs is projected to increase due to climate change. Successful adaptation to ETEs requires an understanding of the contemporary frequency of these events, and their likely occurrence under climate change. However, very little research has been conducted on ETEs in South Africa, and only a few attempts have been made to identify and examine trends. This study addresses this gap in the literature through four key contributions. The first is a review of the published studies on ETEs and their effects in South Africa, providing key methodological and theoretical directions for future research. The second is the first statistical classification of seasonal boundaries in South Africa based on temperature data. This is imperative in facilitating the analysis of seasonal ETEs, and seasonal-resolution trend calculation. The third and fourth contributions involve the calculation of cold and warm ETEs respectively, using the ET-SCI for the first time in South Africa, and comparing the results to those for the ETCCDI. The review of the literature demonstrates the paucity of research in South Africa, and some of the key methodological challenges pertaining to the temporal and spatial resolution of data points; the indices used; and the interpretation of the results. The statistical classification of seasons demonstrates that the majority of the stations can be classified into four distinct seasons, while the statistically classified seasonal brackets include summer (October/November/December/January/February/March), early autumn (April) and late autumn (May), winter (June/July/August), and spring (September). The analyses of ETEs demonstrate that both hot and cold ETEs pose threats to South Africa and reveal a considerable spatial heterogeneity in the trends for each ETE index, providing input towards more effective adaptation planning for the regions under greatest risk.
A thesis submitted in fulfilment of the academic requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Geography, Archaeology and Environmental Studies, University of the Witwatersrand, Johannesburg 2020
Keywords: Extreme temperature events (ETEs); Heatwaves; Cold waves; Seasonal classification